Healthstyle: A Self-Test - Linda B. Bobroff (EDIS)
Revised! FCS8553, a 6-page illustrated fact sheet adapted by Linda B. Bobroff, provides a brief self-test, developed by the Public Health Service, that indicates how well a person is doing in several categories of healthy behaviors recommended for most adult Americans. Published by the UF Department of Family Youth and Community Sciences, June 2010. Minor Revision September 2018.